Understanding of groundwater evolution through chemical and age dating information in the Yongding River alluvial fan in Beijing - Liu, Kai; Qiao, Xiaojuan; Wang, Shanshan; Sun, Ying (Frontiers in Environmental Science, 2022)
Groundwater plays important roles in human community development and the urbanization process as the results of global environmental change and rapid population growth. A clear understanding of the vertical and horizontal spatial distribution characteristics of groundwater and sediment is the premise of efficient groundwater resource management and utilization in alluvial plains. To explore the evolution process of groundwater and the distribution of sediment in the Yongding River (YDR) alluvial fan, a typical profile from Mentougou to Fengheying was chosen to conduct an extensive hydrogeological investigation with multiple hydrochemical, isotopic, and age dating analyses, which represents one of the most typical hydrogeological units in the YDR alluvial fan. The analysis results show that (i) along the profile, the water’s chemistry type gradually changes from HCO3-Ca·Mg to HCO3-Na. The contents of coarse grain gradually decrease while fine particles regularly increase. Also, a similar evolution trend is found in the vertical direction. (ii) The annual renewable rate of groundwater is > 10% in the upper fan, 2%–8% nearby Daxing, and < 2% in Fengheying. (iii) In the proximal fan area, the average flow velocity of the single and double layer is about 65 m yr−1 and of approximately 18.9 m yr−1. From the mid fan to distal fan, the value of velocity and hydraulic conductivity decreases from 12.4 m yr−1 to 3.75 m yr−1 and from 8.54 m yr−1 to 0.64 m yr−1, respectively. (iv) The 14C analysis results indicate that the age of shallow and deep groundwater ranges from 5a to 60a and from 4000a to 12000a, respectively. The groundwater age increases with depth in the vertical direction and increases from northwest to southeast along in the alluvial fan in the horizontal direction. Understanding the evolution process of sediment and hydrochemistry in the YDR alluvial fan provides a valuable reference for groundwater resource development, utilization, and pollution prevention in the alluvial fan.